Stability and Antibiotic Potency Improvement of Levofloxacin by Producing New Salts with 2,6- and 3,5-Dihydroxybenzoic Acid and Their Comprehensive Structural Study - Ilma Nugrahani; Muhammad Ramadhan Sulaiman; Chiaki Eda; Hidehiro Uekusa; Slamet Ibrahim (MDPI AG, 2022)
Recently, solid-state engineering has become a promising approach to improving the stability and potency of antibiotics. Levofloxacin (LF) is a broad-spectrum fluoroquinolone antibiotic marketed in solid and solution dosage forms. However, this substance forms solid hydrates under ambient conditions and degrades due to lighting, which may change its solid properties and dose. In addition, resistance cases have been reported due to long-time antibiotic usage. This research aims to allow LF to react with antioxidant dihydroxybenzoic acid (DHBA), which has low antimicrobial activity, to produce a more stable compound under water and lighting conditions and improve LF's potency. The experiment begins with a screening to select potential DHBA isomers that can react with LF and predict the stoichiometric ratio using phase diagrams, which show that 2,6-DHBA and 3,5-DHBA are prospective antioxidants that can react with LF in a (1:1) molar ratio. Multicomponent systems are prepared by dissolving the LF-DHBA mixture in (1:1) ethanol-methanol (95% grade) and evaporating it. Then, the new solid phase formation is confirmed by thermal analysis and powder X-ray diffractometry. Next, infrared spectrophotometry and neutron magnetic resonance analyses are used to identify the LF-DHBA's interactions. Finally, single-crystal X-ray diffractometry is used to solve the three-dimensional structure of the multicomponent system. We then conduct a hygroscopicity and stability test followed by a lighting and potency test using the microdilution method. Our data reveal that both reactions produce salts, which are named LF-26 and LF-35, respectively. Structurally, LF-26 is found in an anhydrous form with a triclinic crystal packing, while LF-35 is a hemihydrate in a monoclinic system. Afterward, both salts are proven more stable regarding water adsorption and UV lighting than LF. Finally, both multicomponent systems have an approximately two-fold higher antibiotic potency than LF. LF-26 and LF-35 are suitable for further development in solid and liquid dosage formulations, especially LF-35, which has superior stability compared with LF-26.